2019
DOI: 10.3390/ph12040178
|View full text |Cite
|
Sign up to set email alerts
|

Iron as Therapeutic Target in Human Diseases

Abstract: Iron is essential for almost all organisms, being involved in oxygen transport, DNA synthesis, and respiration; however, it is also potentially toxic via the formation of free radicals [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…Our data found no increase in the accumulation of Fe in mice exposed or not to MPTP when comparing young vs. old animals (Figure 3). This data confirmed that increased Fe levels occur throughout the lifetime [31,32,63] and are not detected prior to disease onset [31,32,[40][41][42]. Sequestered in peripheral immune cells, Fe circulates and enters the brain.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our data found no increase in the accumulation of Fe in mice exposed or not to MPTP when comparing young vs. old animals (Figure 3). This data confirmed that increased Fe levels occur throughout the lifetime [31,32,63] and are not detected prior to disease onset [31,32,[40][41][42]. Sequestered in peripheral immune cells, Fe circulates and enters the brain.…”
Section: Discussionsupporting
confidence: 71%
“…Hence, the disruption of Fe homeostasis in the brain strongly contributes to neuroinflammation and sensitizes disease onset, as previously reported [60]. Fe is highly abundant in the brain, where it is involved in many biological functions [32,33,41,42]. Its ability to undergo oxidation and reduction reactions, exchanging electrons with different substrates, turns it potentially toxic.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation